The Comparison of Doxycycline Residue in the Meat of Broiler Chickens Administered in Feed and Water - A D Wijayanti; . Wihandoyo; A W Rosetyadewi (Faculty of Animal Science, Bogor Agricultural University, 2011)
The purpose of this research was to investigate the effect of doxycycline (a tetracycline derivative) administered at disease-prevention dose given daily in the feed and drinking water on the residue level in the broiler-chicken meat. Doxycycline at concentration of 100 ppm was mixed in the drinking water (1 g of doxycycline in 10 L of drinking water) and feed (1 g of doxycycline in 10 kg of feed). Samples of chicken meat were taken every week to measure their residue level. Analysis of doxycycline level was performed using high performance liquid chromatography with extraction method referring to the standard of Association of Official Analytical Chemistry. The result showed that the residue level in the group of chickens given doxycycline through drinking water was higher (P<0.05) than in the group given doxycycline through the feed, except for the result in the 5th week, that showed no significant difference. The highest residue level was found at the first week in the group given doxycycline in drinking water (0.96±0.15 µg/g), while the lowest was found at the sixth week in the group given doxycycline in the feed (0.10±0.01 µg/g). The level of doxycycline residue exceeding the level permitted by the Indonesian National Standard (0.1 µg/g). It can be concluded that doxycycline is not recommended to be given daily both through water or feed to commercial chickens as a disease-prevention agent.